The hourglass model of evolutionary conservation during embryogenesis extends to developmental enhancers with signatures of positive selection - Liu, Jialin; Viales, Rebecca R.; Khoueiry, Pierre; Reddington, James P.; Girardot, Charles; Furlong, Eileen E.M.; Robinson-Rechavi, Marc (Genome Research, 2021)
Inter-species comparisons of both morphology and gene expression within a phylum have revealed a period in the middle of embryogenesis with more similarity between species compared with earlier and later time points. This “developmental hourglass” pattern has been observed in many phyla, yet the evolutionary constraints on gene expression, as well as the underlying mechanisms of how this is regulated, remain elusive. Moreover, the role of positive selection on gene regulation in the more diverged earlier and later stages of embryogenesis remains unknown. Here, using DNase-seq to identify regulatory regions in two distant Drosophila species (D. melanogaster and D. virilis), we assessed the evolutionary conservation and adaptive evolution of enhancers throughout multiple stages of embryogenesis. This revealed a higher proportion of conserved enhancers at the phylotypic period, providing a regulatory basis for the hourglass expression pattern. Using an in silico mutagenesis approach, we detect signatures of positive selection on developmental enhancers at early and late stages of embryogenesis, with a depletion at the phylotypic period, suggesting positive selection as one evolutionary mechanism underlying the hourglass pattern of animal evolution.